Refined numerical simulation of the mechanical behaviour of hollow sphere structures - Sharmugham, Thinesh Kumar (2009)
Metallic Hollow Sphere Structures (MHSS) is a member of cellular metal family which have air cavities while the boundaries are made of solid metals. It offers plenty of advantages and are applicable in many fields such as automotive or architecture. In this project, two major problems pertaining sintered MHSS were studied which are porosity in sphere walls and geometrical imperfection due to contact between spheres. Finite element analysis is the only methodology used in this project. The main objective of this project is to procure the mechanical properties of MHSS by incorporating the effect of these two problems into simulations. The analysis was divided into two parts which are porosity model and sphere model. The porosity models were used to obtain the mechanical properties of base material steel by taking porosity in sphere walls into account. Two different models were generated which are PC (primitive cubic) and FCC (face-centered cubic) which act as idealised porosity. These values were then used in sphere models as the material properties for MHSS. There are two different sphere models which are the 1.6 mm and 2.6 mm model. Geometrical imperfection effect is applied in these models. The simulations were run by mimicking a compression test. Initial findings proved that Young’s modulus, E, yield stress, oY and Poisson’s ratio, u, change with porosity percentage. The appropriate mechanical properties for 1.6 mm and 2.6 mm MHSS were acquired and used in MHSS simulations. Simulation results showed that the material properties decrease from no porosity model to FCC model. However, the difference between simulations and experimental results are big, which means better models need to be built to obtain better results.